Another Covid Causality: Global Journalism - Khan, Ershad Komal (Department of Communications, Universitas Islam Indonesia, 2023)
This study investigates the profound impact of the Covid-19 pandemic on the global media landscape and its consequential effects on journalism. Utilizing the secondary data analysis method, this study explores how the pandemic affected journalists worldwide. The study argues that the Covid-19 pandemic exacerbated media commercialization globally due to the ensuing global recession. Simultaneously, there was a noticeable push by politicians to exert greater influence over the media, seeking to conceal their misdeeds and shortcomings, as well as to propagate their narratives through the press. This encompassed discussions about the coronavirus’s origin, transmission, and containment efforts, often as a means to gain advantages over domestic and international political adversaries. Many outlets, faced with fiscal and political adversity, unwittingly became conduits for such political propaganda, a consequence both of their struggle for survival and their lack of preparedness to navigate a crisis of such magnitude. Consequently, a surge of disinformation and misinformation regarding the virus’s origin and mitigation permeated media outlets, resulting in a crisis of credibility. The aftermath reveals a disheartening decline in public trust in mass media that significantly impeded vaccination initiatives.